Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) pada Materi Sistem Koloid untuk Kelas XI SMA/MA - Rosalia Rosalia; Suryelita Suryelita (Entalpi Pendidikan Kimia, 2021)
ABSTRACT The 2013 curriculum emphasizes students to be active in learning independently, have the skills to think and act, be critical, independent, productive, good cooperation and communicative. One of the curriculum demands can be realized by applying the Problem Based Learning (PBL) model in the learning process. This study aims to produce PBL-based worksheets on colloidal system materials that are valid and practical. The research implementation uses the R&D method. The development stage uses a 4D model consisting of define, design, develop and deploy which is limited to development due to time and cost limitations. The research was conducted by testing the validity and practicality of the resulting LKPD. Based on the research data obtained, 5 validators have a validity of 0.87 with a valid category. Practicality that was carried out to 3 teachers had a value of 91.67% in the very practical category and practicality to 30 students of class XI IPA had a practicality value of 88.5% in the very practical category. Keywords: LKPD, PBL, Colloidal System, R&D